Evaluación de compatibilidad de bases pigmentarias de diferentes químicas de pinturas (2018)
In this document we will observe the behavior of each relationship of concentrations raised, the result of the best pigment paste per color, the mixtures that comparing them with the bases of each chemical are more compatible to reduce time, movements, decrease inventories, lower level of vertimientos and standardize the color for different paint chemistries.